Comparison of hemodynamic response of intravenous lidocaine and esmolol during laryngoscopic intubation under general anesthesia for major abdominal surgery - Manpreet Singh; Basu, Maitraye; Ghosh, Amrita; Pal, Ranabir; Manasij Mitra (Asian Journal of Medical Sciences, 2024)
Background: Many studies have shown the beneficial effect of prophylactic lidocaine or esmolol on hemodynamic response during laryngoscopic intubation. Although many studies observed a better effect of esmolol over lidocaine, some studies have drawn an impression of equal efficacy or even no benefit with the use of either of the drugs. Aims and Objectives: The study aimed to compare the heart rate (HR) at 1 min after intubation between the patients receiving lidocaine and esmolol. Other outcome measures were to compare HR at 3 and 5 min post-intubation and to compare the mean arterial pressure at 1, 3, and 5 min after intubation. In addition, the adverse events, if any, were noted. Materials and Methods: Fifty patients, 30–45 years, either sex, Mallampati grade 1–2, of the American Society of Anesthesiologists physical status I-II, posted for elective abdominal surgery requiring direct laryngoscopic endotracheal intubation were included. Patients were randomly allocated into two groups to receive esmolol 2 mg/kg (Group E, n=25) or 2% lidocaine 2 mg/kg (Group L, n=25), intravenously. HR and mean arterial blood pressure (MAP) were recorded at 1-, 3-, and 5-min interval post-intubation. Results: The mean HR at 1-min post-intubation was considerably lower using esmolol in comparison with lidocaine (91.7±9.7 vs. 107.7±5.1, P≤0.0001). The mean HR and MAP at 3-min and 5-min post-intubation were considerably lower with the use of esmolol compared with lidocaine. Conclusion: Esmolol is better than lidocaine in attenuating the hemodynamic response of intubation.